Interactive learning software for communication engineering subject - Naim, N. F.; bin Nordin, Abdul Hadi; Rahman, H. A. (2011 IEEE International Conference on System Engineering and Technology, 2011)
Learning is becoming more interesting each day. This project highlights an interactive learning system for electromagnetic and communication subjects using MATLAB program and its graphical user interface (GUI). The system needs the user to enter appropriate parameters into blank boxes in the GUI. Then, user can obtain the result by clicking the answer button. The designed program offers varieties of engineering problems such as propagation of waves, electric field intensity, plotting electric field, dot and cross product of vectors for electromagnetic part. While for communication part consists of High Frequency (HF) analysis and digital modulation. In digital modulation, user can generate and observe Amplitude-Shift Keying (ASK) signal and Frequency-Shift Keying (FSK) signal. The programs are user-friendly and have interactive tutorials and can be used as a powerful tool for improving the teaching process. The standalone program for this system has also been developed. Hence, the way of learning will become easier and more interesting.